Different people, different pathways: Human capital redeployment in multi‐business firms - Sabel, Christopher Albert; Sasson, Amir (Strategic Management Journal, 2023)
Abstract Research Summary Multi‐business firms redeploy human capital to strengthen individual business units. However, we know little about the antecedents of such redeployments and their effects on unit outcomes. Contributing to the resource redeployment and strategic human capital literatures, we test the relationships between parent–unit industry relatedness, the direction of redeployment (parent‐to‐unit and unit‐to‐parent), the type of human capital, the likelihood of redeployment, and post‐redeployment unit closure. Using Norwegian population‐level microdata of spinouts, we find that parent–unit industry relatedness increases the likelihood of human capital redeployment and that this effect is stronger for generalists than for specialists. Further, we find that parent‐to‐unit and unit‐to‐parent redeployment of generalists and specialists have distinct effects on unit closure, largely because of differences in post‐redeployment unit performance. Managerial Summary Firms with multiple business units often transfer employees between units to strengthen them. However, we do not know which employees are more likely to be sent and which employees, if any, affect the receiving unit's survival and performance. Analyzing over 9000 spinouts in Norway between 2004 and 2015, we find that employees are more likely to be sent when the parent and the unit are in related industries. We further show that employees with specialized professional knowledge are sent regardless of relatedness, while generalists are sent when industries are related. Regarding post‐transfer unit survival, we find that parent‐to‐unit and unit‐to‐parent redeployment of generalists and specialists have distinct effects on survival, largely because of differences in the impact on post‐transfer unit performance.